Academic tenure, risk-taking and the diversification of scientific research. Issue 7 (3rd October 2017) - Franzoni, Chiara; Rossi-Lamastra, Cristina
Abstract: We discuss two competing hypotheses linking the relative job security granted by tenure in academic employment to scientists' choices between diversifying vs. specialising their research portfolio. To test our hypotheses, we develop a new methodology, using an algorithm of semantic analysis that partitions scientists' publications into research themes, and we compute the Blau's diversification index for 562 scientists observed over 15 years. The results of a Fractional Probit Model with fixed effects show that tenure is associated to more diversification of research interests. We discuss the implications for policy-makers and granting agencies wishing to incentivise explorative research.